On-Line Quantification Of Corrosive Sulphur Content In Large Autotransformers - Ahmad Khiar, Mohd Shahril; Lewin, Paul L.; Pilgrim, James A.; Garcia, Sergio B.; Brown, Richard C. D.; Langley, Graham John; Wilson, Gordon (Institute of Electrical and Electronics Engineers Inc., 2020)
This paper introduces the use of thin film copper strips as a potential approach for online quantification of corrosive sulphur content in transformer insulating oils. The progression of sulphur corrosion is tracked by means of the changes in resistance of the thin film copper strips which is measured based on low-resistance measurements using the four-wire measurement method. The results show that the change of resistance of thin film copper is a function of the level of corrosive sulphur compounds (i.e. in ppm) and the bulk temperature of the oil.